When men fight with women (versus other men): limited offending during disputes - Felson, Richard B. (Criminology, 2023)
What transpires in a dispute, even a violent dispute, is affected by the tendency for adversaries to engage in "limited offending." We focus on one restraint: the tendency of men to limit their aggression in their disputes with women. Analyses are based on an incident-level survey about interpersonal disputes administered to 503 men who are incarcerated and 220 men who had never been incarcerated. Using multinomial and logistic regression models, we examined the extent to which an adversary's gender predicted dispute-related behaviors. The evidence suggests that the chivalry norm has pervasive effects on the behavior of men during their disputes with women. Men are more likely to engage in remedial actions (e.g., apologies) when their adversary is a woman, as opposed to another man. In addition, men are less likely to make violent threats and engage in physical attacks when their adversary is a woman, even after they have themselves been physically attacked. When men are violent, they are less likely to injure a woman than a man. However, the chivalry norm does not inhibit verbal aggression in these disputes: men are just as likely to engage in verbal attacks and nonviolent threats when the adversary is a woman.